2011
DOI: 10.1103/physreve.83.011803
|View full text |Cite
|
Sign up to set email alerts
|

Star copolymers in porous environments: Scaling and its manifestations

Abstract: We consider star polymers, consisting of two different polymer species, in a solvent subject to quenched correlated structural obstacles. We assume that the disorder is correlated with a power-law decay of the pair-correlation function g(x)~x(-a). Applying the field-theoretical renormalization group approach in d dimensions, we analyze different scenarios of scaling behavior working to first order of a double ɛ=4-d, δ=4-a expansion. We discuss the influence of the correlated disorder on the resulting scaling l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 74 publications
0
21
0
3
Order By: Relevance
“…attain appropriate values z u > 0 and z v < 0 only in the unphysical region ε d < 0) and thus, cannot provide estimates of scaling exponents. The same problem appears for the coupling flow functions of the m−vector model with extended defects [35], when one tries to take the m → 0 limit. A similar problem of the absence of stable and physically accessible fixed points exists also in the case of uncorrelated point-like impurities [10,17], but it was solved by adsorbing the interaction with disorder into the excluded volume interaction due to special symmetry [23].…”
Section: Note That R(s) Is a D-dimentional Vector With Unit [Length] mentioning
confidence: 99%
See 1 more Smart Citation
“…attain appropriate values z u > 0 and z v < 0 only in the unphysical region ε d < 0) and thus, cannot provide estimates of scaling exponents. The same problem appears for the coupling flow functions of the m−vector model with extended defects [35], when one tries to take the m → 0 limit. A similar problem of the absence of stable and physically accessible fixed points exists also in the case of uncorrelated point-like impurities [10,17], but it was solved by adsorbing the interaction with disorder into the excluded volume interaction due to special symmetry [23].…”
Section: Note That R(s) Is a D-dimentional Vector With Unit [Length] mentioning
confidence: 99%
“…The influence of such disorder on the critical behavior of magnetic systems with ε ddimensional defects of parallel orientation within frames of the spin m−vector model was analyzed in refs. [32,34,35]. It was shown that there are two characteristic correlation lengths in the system, one parallel and other perpendicular to the defects.…”
Section: Introductionmentioning
confidence: 99%
“…Щобiльше, унiверсальною виявляється i форма таких утворень [28]. Деякi нашi результати в цiй дiлянцi, а також ре-зультати дослiдження конформацiйних властивостей полiмерiв у пористому середовищi [29][30][31] наведенi в роздiлах V-VIII.…”
Section: складнI полIмернi макромолекулиunclassified
“…Застосовуючи пiдхiд теоретико-польової РГ, у ро-ботi [30] ми проаналiзували вплив далекосяжно ско-рельованого безладу (5) на унiверсальнi показники (1) та отримали числовi значення показникiв у ново-му класi унiверсальностi. Важливо зазначити, що на-явнiсть скорельованих дефектiв складної структури спричиняє зростання ефективного розмiру полiмер-ного клубка (збiльшення значення показника ν), i цей ефект посилюється зi зростанням кореляцiй безладу.…”
Section: конформацIйнi властивостI полIмерiв у пористому середовищIunclassified
See 1 more Smart Citation